Systemic administration of epothilone B promotes axon regeneration and functional recovery after spinal cord injury - Ruschel, Jörg; Sliwinski, Christopher; Blesch, Armin; Weidner, Norbert (Science, 2015)
After central nervous system (CNS) injury, inhibitory factors in the lesion scar and a poor axon growth potential prevent axon regeneration. Microtubule stabilization reduces scarring and promotes axon growth. However, the cellular mechanisms of this dual effect remain unclear. Here, delayed systemic administration of a blood-brain barrier permeable microtubule stabilizing drug, epothilone B, decreased scarring after rodent spinal cord injury (SCI) by abrogating polarization and directed migration of scar-forming fibroblasts. Conversely, epothilone B reactivated neuronal polarization by inducing concerted microtubule polymerization into the axon tip, which propelled axon growth through an inhibitory environment. Together, these drug elicited effects promoted axon regeneration and improved motor function after SCI. With recent clinical approval, epothilones hold promise for clinical use after CNS injury.